Efficacy of pembrolizumab in patients with pituitary carcinoma: report of four cases from a phase II study - Siqing Fu; Aung Naing; Filip Janku; Mingxuan Xu; Anas Alshawa; Nazanin Majd; Steven G Waguespack; Marta Penas-Prado; Carlos Kamiya-Matsuoka; Shaan M Raza; Ian E McCutcheon (Journal for ImmunoTherapy of Cancer)
Pituitary carcinoma is an aggressive tumor characterized by metastatic spread beyond the sellar region. Symptoms can be debilitating due to hormonal excess and survival is poor. Pituitary carcinomas recur despite conventional multimodality treatments. Given the recent advances in the use of immune checkpoint inhibitors (CPIs) to treat various solid cancers, there has been interest in exploring the role of immunotherapy for treating aggressive, refractory pituitary tumors. We treated 4 patients with pituitary carcinoma with pembrolizumab as part of a phase II clinical trial. Two patients (patients 1 and 2) with functioning corticotroph pituitary carcinomas (refractory to surgery, radiotherapy and chemotherapy) had partial radiographic (60% and 32% per Immune-Related Response Evaluation Criteria In Solid Tumors, respectively) and hormonal responses. Patient 1’s response continues 42 months after initiation of pembrolizumab and his tumor tissue obtained after treatment with temozolomide demonstrated a hypermutator phenotype with MSH2 and MSH6 gene mutations. Patient 2’s tumor after exposure to temozolomide was not sampled, but prior somatic mutational testing was negative. One patient with a non-functioning corticotroph tumor (patient 3) had a best response of stable disease for 4 months. One patient with a prolactin-secreting carcinoma (patient 4) had progressive disease. The latter 2 patients’ tumors did not demonstrate a hypermutator phenotype after treatment with temozolomide. Programmed death-ligand 1 staining was negative in all tumors. We report 2 cases of corticotroph pituitary carcinoma responsive to pembrolizumab after prior exposure to alkylating agents. The role of CPIs in treating patients with pituitary carcinoma, the relationship between tumor subtype and response to immunotherapy and mechanisms of hypermutation in this orphan disease require further study.Trial registration number: NCT02721732.